Do Elite Universities Pick Sports to Pick Students? Athletic Admissions and SES Targeting - Ahmed El Fatmaoui; Tyler Ransom (Institute of Labor Economics (IZA), 2025)
This study investigates the extent to which U.S. universities strategically use athletic admissions to shape the socioeconomic status (SES) of their student bodies. Using a novel dataset linking NCAA roster data to neighborhood characteristics, we document substantial SES segregation across sports and universities. More selective institutions, particularly elite private universities, allocate up to 30% of enrollment to athletes who typically come from higher-SES backgrounds than their non-athlete peers. However, contrary to popular belief, we find that elite institutions enroll similarly wealthy athletes across all sports. Estimates of our structural model of sports bundle choice reveal that this SES homogeneity across sports limits universities' ability to systematically choose sports offerings to target higher-SES students. Counterfactual analyses demonstrate that athletic enrollment caps would create additional seats for non-athletes but require complementary policies to meaningfully impact socioeconomic mobility.
Keywords: C35; I23; I24; L83; 330; higher education; college athletics; income segregation; university admissions